Narrowing the Global Gap: Eco-Social Market Economy as New Perspective to Deal with Global Economic Inequality and Economic Insecurity in 21st Century - Reza A.A Wattimena; Anak Agung Banyu Perwita (Andalas Journal of International Studies (AJIS), 2017)
Global economic inequality, namely the economic inequality between various countries and regions, is one of the biggest challenges of 21st century. Thus, it has also become an important issue in economic security. It creates extreme poverty in the face of abundant living in several rich countries and regions. It is also the root of other global problems, such as human trafficking, spreads of slums, diseases, and international network of radicalism, extremism and terrorism. Because of the global scope, the world needs to develop new perspective in combating global economic inequality and its negative consequences. Eco-social market economy, which is developed from the German social theories, can offer such perspective. It balances between two important areas of social life, namely social justice on the one hand, and ecological awareness of the other hand. This paper elaborates the basic notions and implementations of eco-social market economy in global level to overcome the issue of global economic inequality in 21st century as a new perspective in addressing the issue of economic insecurity in our current global economic, political and security interactions.